Действие ионного облучения на границу раздела металл-диэлектрик - Шмырин А. И.; Пичугин В. Ф. Владимир Федорович; Франгульян Т. С. Тамара Семёновна; Горностаев А. М.; Тишкина В. А. (Томск, 1993)
Деп. в ВИНИТИ 15.04.93, № 990-В93